The present as the past's future : the heritage significance of foundation deposits and time capsules in Christchurch : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Arts in Museum Studies at Massey University, Manawatū, New Zealand - Adamski, Maria Ann (Massey University, 2019)
Foundation deposits and time capsules (collectively deposits) are hidden vessels containing purposefully gathered objects to be opened in the future. This thesis examines the importance of this type of artefact within a heritage significance evaluation methodology. Deposits are of interest as they are a representative record of their time selected by communities for preservation. They have not been thematically identified or considered for protection by territorial authorities and therefore are not listed in District Plans. This thesis focuses on deposits at two different locations, the Godley Statue and the Sumner Borough Council Chambers, which were exposed as a result of the Canterbury Earthquakes 2010-11. It also focuses on the modern deposits that were subsequently placed at these sites. In considering these objects this research asks how are these deposits valued and how does this contribute to their significance. The aims of this study are to determine the values associated with these deposits and critically appraise the effectiveness of a territorial heritage assessment method. The research is based on reviewing archival documents, historic records and ceremonial speeches along with an examination and assessment of the objects. The contemporary importance of the object’s is understood through interviewing individuals who had experiential knowledge. The ceremonial speeches and interviews are analysed using an inductive reasoning and adapted grounded theory approach to elicit a core value. This research demonstrates that a participatory process contributes to a greater understanding of New Zealand’s heritage that may not be immediately obvious. It establishes that deposits are valorised and justify increased attention as they have the potential to afford insight into the past, the present and the future. As a result it is essential that they are understood before they are responded to. Further it was found deposits challenge traditional heritage practice. This research suggests increased attention is required towards assessing social values and to evaluating them as a separate criterion.
Figures are re-used with permission.
Keywords: Time capsules; New Zealand; Christchurch; History; Antiquities; Sources; Social aspects; 430202 Critical heritage, museum and archive studies